MtDNA deletions and aging - Sprason, Charlotte; Tucker, Trudy; Clancy, David (Frontiers in Aging, 2024)
Ageing is the major risk factor in most of the leading causes of mortality worldwide, yet the fundamental causes mostly remain unclear. One of the clear hallmarks of ageing is mitochondrial dysfuncon. Mitochondria are best known for their roles in cellular energy generaon but are also crical biosynthec and signalling organelles. They also undergo mulple changes with organismal age, including increased genec errors in their independent, circular genome. A key group of studies looking at mice with increased mtDNA mutaons showed that premature ageing phenotypes correlated with increased deleons but not point mutaons. This generated interest in mitochondrial deleons as a potenal fundamental cause of ageing. However, subsequent studies in different models have yielded diverse results. This review summarises research on mitochondrial deleons in various organisms to understand possible roles in causing ageing whilst idenfying key complicaons in quanfying deleons across all models.